High concentrations of middle ear antimicrobial peptides and proteins and proinflammatory cytokines are associated with detection of middle ear pathogens in children with recurrent acute otitis media. - Elke J Seppanen; Ruth B Thornton; Karli J Corscadden; Caitlyn M Granland; Julie Hibbert; Angela Fuery; Selma P Wiertsema; Shyan Vijayasekaran; Harvey L Coates; Peter Jacoby; Andrew Currie; Peter C Richmond; et al. (PLoS ONE)
Recurrent and chronic otitis media (OM) are often refractory to antibiotics due to bacterial persistence in biofilm within the middle ear. In vitro and in vivo studies have demonstrated that antimicrobial proteins and peptides (AMPs) are bactericidal against otopathogens, indicating potential therapeutic value for recalcitrant OM. We measured concentrations of 6 AMPs and 14 cytokines in middle ear effusion (MEE) from 67 children undergoing ventilation tube insertion for recurrent acute OM. Sixty one percent of children had bacterial otopathogens detected in their MEE, 39% by PCR and 22% by PCR and culture. Groups were defined as: PCR-negative/culture-negative (absence of bacterial otopathogen), n = 26; PCR-positive/culture-negative (presence of nonculturable bacterial otopathogen), n = 26; PCR-positive/culture-positive (presence of culturable bacterial otopathogen), n = 15. Age, antibiotic usage, day-care attendance, presence of respiratory viruses in MEE and number of AOM episodes were similar between groups. AMP and cytokine concentrations were higher in children with bacterial otopathogens in their MEE compared to those with no bacterial otopathogens. Median concentrations of AMPs (except HBD2) were 3 to 56-fold higher in MEE from children with bacterial otopathogens detected in their MEE (P ≤ 0.01). Similarly, median cytokine concentrations (except TGFβ) were >16-fold higher in MEE with bacterial otopathogens detected (P ≤ 0.001). This is the first study to measure AMPs in MEE and together with the cytokine data, results suggest that elevated AMPs and cytokines in MEE are a marker of inflammation and bacterial persistence. AMPs may play an important role in OM pathogenesis.